Soil Solarization for Management of Seedling Diseases of vegetables in nursery - Singh, Deepak; Singh, Ajay Kumar; Singh, Anil Kumar (Indian Farming, 2015)
Solarization involves limitations, difficulties and potential negativeeffects. It can be used in regions where the climate is suitable and soil is free of crops for about one month or more at the time of mulching. It is too expensive for some crops and ineffective in the control of certain diseases. Heat tolerant pathogens might develop after repeated application.